Technical efficiency analysis of shrimp farming in Peninsular Malaysia: a stochastic frontier production function approach - Md. Nurul Islam, Gazi; Tai, Shzee Yew; Mohd Noh, Kusairi (Academic Journals, 2014)
Shrimp farming has become increasingly important in the aquaculture industry of Peninsular Malaysia. The culture areas for shrimp continue to expand with a view to achieve higher output and generating more export earnings. This paper uses farm level data gathered from Perak and Johor States of Peninsular Malaysia to investigate the technical efficiency of brackish water shrimp farms. Stochastic frontier production analysis is applied to examine the determinants of frontier production function and the technical efficiency of pond shrimp farming system. On average, 65% of the sampled shrimp farms are technically efficient. The results suggest high degrees of technical inefficiency exist among the shrimp farmers. This implies that great potential exists to increase shrimp production through improved efficiency in farm management in Peninsular Malaysia. Initiatives to undertake extension programmes at the farm level are needed to help shrimp farmers in utilizing their resources more efficiently in order to substantially enhance their shrimp production.